The use of fragments of thin veneers as a restorative therapy for anterior teeth disharmony: A case report with 3 years of follow-up - Okida, Ricardo Coelho [UNESP]; Filho, Aljomar José Vechiato [UNESP]; Barão, Valentim Adelino Ricardo [UNESP]; Santos, Daniela Micheline dos [UNESP]; Goiato, Marcelo Coelho [UNESP] (Jaypee Brothers Medical Publishing, 2012)
Aim: The present case report described the use of contact lens of thin porcelain veneers as a restorative therapy to solve anterior teeth disharmony. Background: Fragments of thin veneers are minimally invasive restorations with little or no dental preparation and present thickness ranging from 0.2 to 0.5 mm. They are used in case of diastema closure, small changes of teeth, color and restoration of teeth with small fractures. Case report: A 25-year-old man was admitted at a dental clinic complaining about the diastema presence on the upper anterior teeth. Patient was referred to an orthodontic treatment in order to provide better distribution of the diastemas and harmonious proportion of the teeth. Afterwards, contact lens of thin porcelain veneers were fabricated on the six upper anterior teeth. Conclusion: Based on the outcomes of this clinical report, we considered the use of fragments of thin veneers as a successful treatment option after 3 years of follow-up. Clinical significance: The fragments of thin veneers have been established to be an interesting alternative to esthetically restore the anterior teeth with minimal invasiveness. However, since it is a new treatment modality, longitudinal studies are necessary to understand the material's behavior.
Keywords: Clinical case; Dental contact lens; Dental esthetic; Diastema; Oral rehabilitation; Porcelain; adult; case report; dental porcelain; dental procedure; dental surgery; dental veneer; diastema; follow up; human; male; methodology; Adult; Dental Porcelain; Dental Restoration, Permanent; Dental Veneers; Esthetics, Dental; Follow-Up Studies; Humans; Male